Ethiopia Alive & Thrive Baseline Survey 2010: Volunteer Community Health Promoters - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the volunteer community health promoters (VCHP) survey that was conducted to gather data at baseline as a part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions, delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of IYCF practices in two regions where the IFHP operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The Ethiopia baseline survey had two broad objectives. The first objective was to gather data on the primary impact indicators of the evaluation, prior to implementation of any A&T interventions, to establish a baseline against which changes would be measured. The second objective was to assess different factors that may influence the outcomes of interest, and thus shape the impact of the primary impact indicators. These factors were determined at five different levels: 1) child, 2) maternal/caregiver, 3) household, 4) community, 5) health care providers, 6) health system. These factors will also provide useful information to interpret the results of the impact evaluation and also signal key issues to pay attention to in the process evaluation. The Ethiopia baseline survey used five separate questionnaires that aimed to capture elements along the program impact pathways. These tools include 1) a household questionnaire, 2) a staff questionnaire of HEWs, 3) a staff questionnaire of supervisors of HEWs, 4) a VCHP), and 5) a community questionnaire. Three types of health staff questionnaires (HEW, VCHP, and supervisors) were applied to health staff who are closest to the community or work in the community. In the Health Extension Program (HEP), the key frontline health workers (FHWs) are the health extension workers (HEWs). In addition to HEWs, HEP has invested in developing community volunteers known as Volunteer Community Health Promoters (VCHP), who are trained by HEWs. This volunteer position, although not directly a part of the health system, is nevertheless integral to providing essential health care at the community level. The volunteer community health promoters (VCHP) questionnaire, along with the other two health workers questionnaires (HEW and supervisors), aimed at assessing three major issues: 1) frequency of interactions between health staff and caregivers, and avenues for these interactions; 2) content of the discussion between caregivers and health staff, and the time spent on IYCF-related discussions; and 3) knowledge and training received by the health staff on IYCF. In addition, the frontline health worker questionnaires capture the organizational context within which FHWs deliver their interventions. These are captured by inclusion of questions on perceptions related to their workload and their level of satisfaction with their overall job. This is particularly important to capture volunteer workers who receive no salary.